2013
DOI: 10.5430/jst.v3n2p50
|View full text |Cite
|
Sign up to set email alerts
|

Laser Photobiomodulation as a Potential Multi-Target Anticancer Therapy-Review

Abstract: Background: Anticancer drugs directed at single specific molecular targets tend to induce transitory responses, followed by relapses. Laser photobiomodulation may offer the possibility of targeting multiple hallmarks of cancer by using fit-for-purpose electromagnetic (EM) energy aiming to restore homeostasis-homeokinesis. Methods/Principal Findings: A literature search of English-language articles in five databases (Medline, ISI Web of Knowledge, Cochrane, Google Scholar, Scirus) was conducted using search ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 83 publications
1
8
0
1
Order By: Relevance
“…As we will see, burned rat tissue monitored by proton nuclear magnetic resonance transverse relaxation times and correlation times show significantly enhanced water structuring post IPLD treatment. [20][21] In addition, the micro densitometry of T2 weighted tumor heterogeneities from the phase I trial in patients with advanced neoplasias 16 and an algorithm for tumor characterization also show significantly increased water structuring 18 , consistent with an effect over the exclusion zone associated with histologically-confirmed selective photo-induced tumor cell death. 15 Using a 90MHz nuclear magnetic resonance spectrometer, we found that the IPLD induced significant short-term molecular changes in burned rat soft tissue.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…As we will see, burned rat tissue monitored by proton nuclear magnetic resonance transverse relaxation times and correlation times show significantly enhanced water structuring post IPLD treatment. [20][21] In addition, the micro densitometry of T2 weighted tumor heterogeneities from the phase I trial in patients with advanced neoplasias 16 and an algorithm for tumor characterization also show significantly increased water structuring 18 , consistent with an effect over the exclusion zone associated with histologically-confirmed selective photo-induced tumor cell death. 15 Using a 90MHz nuclear magnetic resonance spectrometer, we found that the IPLD induced significant short-term molecular changes in burned rat soft tissue.…”
Section: Figmentioning
confidence: 99%
“…Along the way, we have proposed detailed mechanisms that explain one basic premise: that external electromagnetic energy supplementation can enhance and even substitute for endogenous ATP production to power and modulate physiologically reparative mechanisms which can help reestablish homeostasis / homeokinesis, even when physiologic metabolic pathways have been compromised. [17][18] Cellular and molecular basis for water-mediated, long-range, energy supplementation aimed at inducing and modulating physiologically reparative processes, including apoptosis, have been described as part of a mechanism called Photo Infrared Pulsed Biomodulation. 5 The role of water as an oscillator in near infrared laser photobiomodulation has also been documented, adding to a more coherent description of the central effects of NIR light over redox centers and key transmembrane enzymes, such as CcO.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we describe a paradigm shift or ''quantum leap'' in the understanding and use of light and its interaction with water and other relevant photoacceptors to control biologic function in medicine through photobiomodulation (PBM) therapy. We propose that progress will lead to the imminent inception of PBM therapy as a mainstream treatment for multiple complex diseases, including solid tumors, as well as neurodegenerative diseases (NDs) of the eye and central nervous system (CNS) [6][7][8][9][10] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%